Perceptions of Universiti Teknologi MARA (UiTM) Melaka students about the importance of Islamic inheritance law (Fara’id) / Norsuhaiza Md Said and Isma Emilia Esa - Md Said, Norsuhaiza; Esa, Isma Emilia (2014)
Islamic Inheritance Law (Fara’id) is among the first discipline to be deprived by God from every single human. This shows how important the knowledge is. Lack of concern attitude among Muslims nowadays, may gradually lead to the loss of this knowledge until it creates conflicts and doubt in God’s justice by disputing rights between genders. This study was conducted to investigate students’ level of knowledge and understanding towards Islamic Inheritance Law and also to study students’ perception towards the importance of this knowledge in life. The research involved respondents from UiTM Melaka. The research instrument used was questionnaire that comprised 48 items, which was conducted by the researcher. Researcher used Statistical Package for Social Science version 22.0 (SPSS) software to analyse raw data to get the frequency, percentage and mean. The research findings showed that respondents’ perception relating to the importance of Islamic Inheritance Law was at high level. Meanwhile respondents’ level of knowledge and understanding towards Islamic Inheritance Law was at average level. At the end of this study, several proposals had been proposed to increase the level of knowledge and understanding of Islamic Inheritance Law among the students as well as society. Further research also had been proposed for the future.